A gecko-inspired wall-climbing robot based on vibration suction mechanism. (October 2019) - Chen, Rui; Fu, Leilei; Qiu, Yilin; Song, Ruizhou; Jin, Yan
A prototype of gecko-inspired wall-climbing robot based on vibration suction mechanism is proposed. The robot adheres to the wall surface based on a novel negative pressure technology named as vibration suction. According to the theory of vibration suction, the vibration suction module is designed as the foot of the wall-climbing robot. In addition, the tripod gait of geckos is taken into account in the motion planning of the robot. By combining the unique properties of vibration suction mechanism and the tripod gait of the geckos, several advantages including stable motion, certain load capacity, anti-overturning ability, and good suction force to the wall surfaces are obtained. The climbing ability is verified by the experiment on the surface of the glass, which manifests that the robot can climb vertically at the highest speed of 13.75 mm/s with a spot turning at the single maximum turning angle of 20°. Potential applications of this proposed climbing robot in some fields include repair, construction, cleaning, and exploration.